PENGARUH TAX AVOIDANCE, VOLUNTARY DISCLOSURE TERHADAP COST OF DEBT DENGAN DEWAN KOMISARIS SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Afdhal Fuad; Kamaliah Kamaliah; Haryani Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aimed to examine the influence tax avoidance and voluntarydisclosure by board of commissioners. The population taken in this study weremanufacturing companies listed on the Indonesia Stock Exchange in 2015-2017which amounted to 135 companies. From this population, there were 93companies as samples in three years. Data obtained using purposive samplingmethod and financial distress were measured using the Model z-score. This studyuses moderated regression analysis (MRA), using SPSS 25 software to processdata. The results of the study show that, (1) Tax avoidance had affect on cost ofdebt (2) Voluntary disclosure had affect on cost of debt (3) Board ofcommissioners able to moderate the affect of tax avoidance cost of debt (4 Boardof commissioners are not able to moderate the affect of voluntary disclosure tocost of debt.Keywords : tax avoidance, voluntary disclosure, cost of debt, board ofcommissioners.